Synthesis, characterization, and cytotoxicity evaluation of polyethylene glycol-coated iron oxide nanoparticles for radiotherapy application - Madhuri Anuje; Padmaja N Pawaskar; Vishwajeet Khot; Ajay Sivan; Satish Jadhav; Jagruti Meshram; Balu Thombare (Journal of Medical Physics, 2021)
Background: Treatment methods for cancer that are widely being utilized affect both normal and cancerous cells. We report synthesis polyethylene glycol (PEG)-coated Fe3O4 nanoparticles (NPs) and its characteristic properties and appraise its potential as a promising radiation sensitizer candidate in radiotherapy that improves cancer treatment and reduces side effects of radiation. Materials and methods: PEG-coated Fe3O4 NPs were synthesized by chemical coprecipitation method and characterized by studying their size, structure, functional group, stability, magnetization, and cytotoxicity using different techniques. X-ray powder diffraction, Fourier transform infrared spectroscopy, and thermogravimetric analysis results show that Fe3O4 NPs have been functionalized with PEG molecules during the course of synthesis. Results Synthesized NPs have good stability based on zeta-potential study. Dynamic light-scattering results reveal that PEG-coated Fe3O4 has a greater hydrodynamic size than bare Fe3O4. Transmission electron microscopy (TEM) micrograph exhibited that NPs are roughly spherical with size in range of 10–20 nm. Saturation magnetization value of PEG-coated and bare Fe3O4 also confirms coating and shows superparamagnetic behavior. Cytotoxicity evaluation study indicated that PEG-coated Fe3O4 is biocompatible on L929 and toxic on Michigan Cancer Foundation-7 (MCF-7) (breast cancer cells). Conclusion: These characterized properties of PEG-coated Fe3O4 NPs show that it could be used as a potential radiosensitizer candidate in radiotherapy to significantly improve cancer treatment and minimize painful side effects of radiation.